Supply chain innovations and partial ownership - Matthias Hunold; Shiva Shekhar (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
We show that competing downstream firms may rather invest in their inefficient inhouse production than help improve the technology of the efficient supplier, even if this is costless. Even worse, a downstream firm can have strong incentives to decrease the efficiency of the supplier in order to improve its outside options. We demonstrate that non-controlling partial backward ownership can align the incentives of the supplier and its customers with respect to supply chain innovations.
Keywords: L22; L40; 330; knowledge spillover; innovation; minority shareholdings; supply chain efficiency; vertical partial ownership